The Francisco Arcellana Library a case study of the conservation practices on the videotape collection - Lopez, Clarisse T.; Granda, Yolanda C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
The Francisco Arcellana Library caters to the courses in Communication, Arts and Literature of the Department of English and Comparative Literature, under the College of Arts and Letters in the University of the Philippines Diliman. The Library videotapes provide film viewings for a holistic view of the lessons discussed in the classroom. Due to frequent use, the materials, in turn, become susceptible to immediate deterioration. Videotapes are delicate materials bearing information and, if not properly maintained, their physical condition could easily be corrupted. What does the Library do to help prolong the use of the videotapes?
This case study determined the practices of the Francisco Arcellana Library in maintaining its videotape collection and whether these conform to the standard conservation practices for videotapes. Conservation practices mean carrying out preventive or preservation measures to halt videotape deterioration and familiarizing with the restoration measures needed to be done for a deteriorated material.
Findings reveal that the current conservation practices of the library do not conform to standard conservation practices. The problems encountered are due to the following factors: absence of conservation policy and guidelines, inadequate financial support from management, lack of basic knowledge of the library personnel on conservation practices, inadequate facilities, uncontrolled environment and absence of tools or reference materials in the Library on standard conservation practices for videotapes.
The recommendations presented include a detailed enumeration of standard preservation and restoration practices to be followed, emphasis on the need for management support, the creation of a Conservation Committee, and the formulation of a written Conservation Policy. Training of the staff and the provision of adequate facilities are also recommended.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Francisco Arcellana Library; Video recordings -- Conservation and restoration